Kampania negatywna, czy nieistniejący „czarny” PR, jako metody dyskredytowania przeciwnika politycznego - Noremberg, Damian (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The difference between a negative campaign and a dirty one is clearly defined. The mechanisms of a dirty campaign cannot be named ‘black PR’ as this does not exist and any member of an election committee who employs such methods to discredit their opponents should not be called a public relations specialist at all. It is to be hoped that we will see a reality where anybody running a dirty campaign will bear the consequences of their activities and be eliminated from the ranks of this magnificent profession dealing with social communication in politics, and from any other activity applying PR tools.